PERAN AMILITE GCK-12H SEBAGAI SURFAKTAN PADA FORMULA SHAMPO: KAJIAN STABILITAS BUSA DAN EFEKTIVITAS PEMBERSIHAN - Nia Yuniarsih; Neni Sri Gunarti; Iin Lidia Putama Mursal; Tiara Maharani Angeline; Ermi Abriyani; Maulana Yusuf Alkandahri; Farhamzah Farhamzah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Shampoo functions to clean hair and scalp and is generally formulated using Sodium Lauryl Sulfate (SLS) surfactants, which are associated with irritation and unstable foam. Surfactant selection is therefore a critical factor in shampoo formulation, as it influences foam production, softness, hair moisture retention, environmental friendliness, and cleansing effectiveness. Amino acid–based surfactants such as Amilite GCK-12H offer advantages including low irritation potential, good foam stability, and biocompatibility. This study aimed to evaluate the effect of Amilite GCK-12H concentration on cleaning power and foam stability in shampoo formulations. The study was conducted by formulating shampoos and performing accelerated stability testing, including pH, viscosity, organoleptic properties, spreadability, homogeneity, foam stability, and cleaning effectiveness. Four formulations were prepared: F0 without Amilite GCK-12H, F1 containing 5%, F2 containing 10%, and F3 containing 15% Amilite GCK-12H. Organoleptic evaluation showed stable odor and homogeneity in all formulations, although color changes occurred in samples exposed to sunlight. pH testing indicated that all formulations remained within the acceptable range of 5.0–9.0, despite slight decreases under certain storage conditions. Viscosity increased at room temperature but decreased at elevated temperatures. Homogeneity and spreadability tests met standard requirements for shampoo preparations. Formulation F3 demonstrated the best performance in foam stability and cleaning effectiveness, achieving a cleaning efficiency of 62% on day 30. Overall, Amilite GCK-12H proved effective in producing a stable shampoo formulation with improved foam characteristics and cleansing performance. These findings support its potential application as a mild, high-performance surfactant for sustainable cosmetic shampoo development in future industrial formulations globally.